Transformations of El Olivar Forest: the way toward landscape conservation - Ruiz, Marino (Universidad de Lima. Carrera de Arquitectura, 2021)
DOI: https://doi.org/10.26439/limaq2021.n007.5181 Urban landscape is the territorial component of cities, which is linked to the human component that perceives and values it accordingly. El Olivar Forest of San Isidro district, an emblematic public space in the city of Lima, stands out for its landscape qualities, which have not been valued beyond its mere aesthetic importance. This article shows the constant transformations it has undergone, which are related to the perception of the urban landscape, the use of the forest and the occupation of the place that occurred during the urban expansion of Lima. The importance of El Olivar Forest goes beyond the simple aesthetic perception of the user: it consists in the relationship built through time between landscape and city, and in the reflections around this relationship. The old olive grove forest offers us nowadays the opportunity to rethink our position regarding its landscape value, both for users and for the city as a whole. Thus, we will be able to identify the actions that will allow its protection and conservation. Such conservation enables us to achieve an adequate balance between nature and citizenship, the raison d'être of a sustainable urban environment.